Population Increase of Muskoxen on Banks Island and Implications for Competition with Peary Caribou - Vincent, D.; Gunn, A. (ARCTIC, 1981)
Surveys were flown in March 1979 and 1980 north and south of 73 deg. N on Banks Island to estimate numbers of muskoxen. Observed total was 11809 animals and estimated population was 18328 muskoxen, suggesting that the population has continued to expand since previous surveys in the early 1970s. A comparison with previous surveys of densities between the north and the south of the island indicates muskoxen have spread from the Thomsen River valley to the northeast and the south. Comparisons with muskox and caribou populations in Alaska and with reindeer in Greenland suggest that co-existence between these species is normal and does not involve competition.